Impact of an evidence-based guideline on the management of community-acquired bacterial meningitis: a prospective cohort study. (November 2016) - Costerus, J.M.; Brouwer, M.C.; Bijlsma, M.W.; Tanck, M.W.; van der Ende, A.; van de Beek, D.
Abstract: Objectives: To study the impact of an evidence-based guideline on the management of community-acquired bacterial meningitis. Methods: We performed an interrupted time series analysis in a prospective nationwide cohort study from 2006 to 2015. The guideline stresses the importance of cranial imaging before lumbar puncture (LP) in selected patients based on clinical criteria, and early treatment with amoxicillin and a third-generation cephalosporin for adults with suspected community-acquired bacterial meningitis. The guideline was published in April 2013. Results: We included 1326 episodes before and 210 episodes after guideline introduction. Cranial imaging was performed before LP in 497 (84%) of 591 episodes with clinical criteria warranting computed tomography (CT). The guideline did not improve this (increase of 2%; 95% confidence interval (CI), −15 to 19). Without these criteria, imaging before LP occurred in 606 (67%) of 900 episodes, also without effect of the guideline (increase of 1%; 95% CI, −25 to 28). The estimate of effect of the guideline for treatment with the recommended antibiotic regimen was an increase of 19.5% (95% CI, 13.5 to 25.5), and there was a trend towards more frequent initiation of treatment before CT. There was no association between delay in antibiotic treatment due to imaging before LP and unfavourable outcome (odds ratio, 1.14; 95% CI 0.86 to 1.52). Conclusions: Cranial imaging is performed before LP in the majority of patients with bacterial meningitis, irrespective of guideline indications. The guideline introduction was associated with a trend towards early initiation of treatment before imaging and with increased adherence to antibiotic policy.